Microinfusion of Pituitary Adenylate Cyclase-Activating Polypeptide into the Central Nucleus of Amygdala of the Rat Produces a Shift from an Active to Passive Mode of Coping in the Shock-Probe Fear/Defensive Burying Test. (14th June 2007) - Legradi, Gabor; Das, Mahasweta; Giunta, Brian; Hirani, Khemraj; Mitchell, E. Alice; Diamond, David M.
Abstract : High concentrations of pituitary adenylate cyclase-activating polypeptide (PACAP) nerve fibers are present in the central nucleus of amygdala (CeA), a brain region implicated in the control of fear-related behavior. This study evaluated PACAPergic modulation of fear responses at the CeA in male Sprague-Dawley rats. PACAP (50–100   pmol) microinfusion via intra-CeA cannulae produced increases in immobility and time the rats spent withdrawn into a corner opposite to the electrified probe compared to controls in the shock-probe fear/defensive burying test. Shock-probe burying and exploration, numbers of shocks received, locomotion distance, and velocity were all reduced by intra-CeA PACAP injection. Further, intra-CeA PACAP effects were manifested only when the animals were challenged by shock, as intra-CeA PACAP injections did not cause significant changes in the behaviors of unshocked rats. Thus, intra-CeA administration of PACAP produces a distinct reorganization of stress-coping behaviors from active (burying) to passive modes, such as withdrawal and immobility. These findings are potentially significant toward enhancing our understanding of the involvement of PACAP and the CeA in the neural basis of fear and anxiety.